Value of urinary CD80 in differentiating minimal change disease from focal segmental glomerulosclerosis - Phuong Anh Le-Thy; Kiem Hao Tran; Thuy Yen Hoang-Thi; Minh Phuong Phan-Thi; Diem Chi Nguyen-Thi; Huu Son Nguyen (Romanian Journal of Pediatrics, 2024)
Background. Minimal change disease (MCD) and focal segmental glomerulosclerosis (FSGS) are two common forms of childhood nephrotic syndrome (NS). Separating MCD from FSGS is essential to determine the treatment therapy and the prognosis. Cluster of differentiation 80 (CD80) in urine is now considered a valuable marker for detecting MCD. Therefore, we conducted this research to evaluate the role of urinary CD80 concentrations in differentiating MCD from FSGS. Methods. A cross-sectional descriptive study was performed on 67 children with NS who underwent kidney biopsy and 67 children in the control group. Results. MCD accounted for the majority (61.2%), while FSGS accounted for 38.8% with an MCD/FSGS ratio of 1.6:1. There were no significant differences in age, gender, hematuria, hypertension, urinary protein-creatinine ratio, and albumin concentrations between the two study groups (p>0.05). There were statistically significant differences in glomerular filtration rate (GFR) between the two study groups with p<0.05. The urinary CD80/creatinine ratio in the MCD group was 25.6 (5.4-38.3) pg/µmol, which was significantly higher than that of the FSGS group (3.6 (1.9-6.5) pg/µmol) with p<0.05. The area under the ROC curve for urinary CD80/creatinine ratio in the diagnosis of MCD with FSGS was 0.87 (95% CI 0.79-0.95) at a cut-off value of 4.6 pg/µmol, with a sensitivity of 85.4% and specificity of 73.1%, p<0.05. Conclusion. The urinary CD80/creatinine ratio was useful in differentiating between nephrotic syndrome with MCD and FSGS.